PENGARUH KINERJA AUDITOR, TURN OVER INTENTION, DAN KOMITMEN ORGANISASI TERHADAP PREMATURE SIGN- OFF (Ditinjau dari Goal Setting Theory) (Proceeding Fakultas Ekonomi, 2012)
Goal Setting Theory in this study is used to review and analyze the influence ofinternal individual factors (such as auditor individual performance, turnover intentionand organizational commitment) on acceptance of a premature sign-off. Source of datain this study were auditors working in audit firms in Indonesia as respondents. The datawas collected using survey method by sending questionnaires to the respondents bymail. The result of this study has shown that individual performance and turnoverintention have influence to acceptance of a premature sign-off. On the other handorganizational commitment has no influence to acceptance of a premature sign-off.Keywords: Goal Setting Theory, Auditor Performance, Turnover Intention,Organizational Commitment, and Premature Sign-off.